Who is the Adolescent Environmentalist? Environmental Attitudes, Identity, Media Usage and Communication Orientation. Issue 4 (4th July 2017) - Nelms, Carrie; Allen, Myria W.; Craig, Christopher A.; Riggs, Shelby
ABSTRACT: There has been an increase in scholarly attention to adolescents' environmental attitudes; however, only a small number of empirical studies address the Adolescent Environmentalist's (AE) personal and collective identity, media usage, and communication orientation. In this study, we investigate differences in young people (aged 12–17) who identify themselves as environmentalists, or the AEs, and those who do not drawing from a national sample of 1096 youth. Results show AEs significantly differ from their peers. The AEs have a different environmental value set, report greater self-confidence and influence among peers, support the stronger display of citizenship behaviors, follow certain news topics more, use and discuss the news more with a variety of others, and report engaging in more dialogue and persuasion.